Ratu Zalecha: Social Construction, Women's Leadership and a Critical Study in the Context of Modern Leaders - Siti Muflichah; Rochmatunnisa Rochmatunnisa; Annida Afifah (Management of Education: Jurnal Manajemen Pendidikan Islam, 2026)
This study examines how women’s leadership in South Kalimantan is socially constructed and how Ratu Zalecha functions as a cultural-historical source of leadership legitimacy for contemporary female leaders. Drawing on social construction theory and feminist leadership perspectives, this study explores the ways in which leadership meanings are shaped by competence, institutional recognition, gendered expectations, and local historical memory. A qualitative case study design was employed, involving four female leaders in educational and organizational contexts in South Kalimantan. Data were collected through semi-structured interviews and analyzed using Miles and Huberman’s interactive model of data condensation, data display, and conclusion drawing. The findings reveal three main themes: leadership is constructed as a relational and contextual practice; female leaders negotiate layered challenges related to gender stereotypes, seniority, emotional expectations, and organizational legitimacy; and Ratu Zalecha serves as a symbolic model of courage, patience, resilience, moral integrity, and transformative influence. This study contributes to social construction and feminist leadership scholarship by showing that women’s leadership legitimacy is produced not only through organizational competence, but also through cultural memory and historically rooted narratives of female agency. The findings suggest that local female historical figures can strengthen women’s leadership identity and provide culturally relevant models for promoting gender-equitable leadership in educational and organizational settings.